Canopy versus epigeal beetle species differential diversity and feeding ecological characteritics employing light-based trapping methods across different oil palm age stand types - Ahmad Bukhary Ahmad Khair,; Mohd Fauzi Mohd Muzamil,; Ruslan Md Yusop,; Noor Hisham Hamid,; Mohd Yusri Mohd. Naser,; Izfa Riza Hazmi,; Abu Hassan Ahmad,; Idris Abdul Ghani, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Suitability of canopy-height light trap tailored from both primary and secondary tropical forests was compared with the newly modified pit-light trap within the context of oil palm plantation of various age stand types and across different seasons. Beetle species were chosen as the representative of other insects within oil palm plantations as to evaluate the effectiveness of both trapping methods. Results showed that the canopy-height light trap employed over the canopy stratum of the selected oil palm age stands produced unstable and unreliable data, with characteristics of overlapping beetle species communities along significant ordination gradients. Modified pit-light trap, on the other hand, showed clear separations of beetle species community structures between younger-older oil palm age stands along significant ordination gradients, as well as accurate divisions of beetle species ecological feeding groups corresponded to different oil palm age stand types and seasons, and acceptable diversity levels. The modified pit-light trap, employed on the epigeal stratum of selected oil palm plantations, paralleled with most anthropogenic and naturally occurring microhabitats, could reduce the risks of attracting unintended beetle species from unrelated oil palm age stand types, as well as possible surrounding secondary tropical forests. It is proposed that the modified pit-light trap to be applied officially for improved evaluations of insect species’ diversity and ecological attributes within oil palm agro-ecosystems.